The Genre of Moral Though in Nahj al-Balagha and its Educative Implications - roohollah shahryary; reza HashemiPaykar; hosein diba (اخلاق وحیانی)
Using the moral and educational knowledge needs understanding of the objectives of Imam Ali (p.b.u.h) to declare the implication of speeches of the Imam without semantic confusion. This paper has been written for this paper to analyze the speeches of the Imam, using the descriptive-analytical method, and discover the general theme and though of Imam Ali (p.b.u.h) concerning normative ethics, and by considering it, it finds the methodical implications of it. The result of this paper shows that the Imam considers the consequences and results of one action as the criterion for its necessity or non-necessity, in the way that moral virtues and vices gain their moral truth or falsity from their results. From other hand, the narrations seem to show virtuous views, suggesting a teleological though, and has no implication on virtuous view. The teleological view of the Imam is significant, since the beginning and the end of this final movement is the unity of God, and might be called the monotheistic teleology. On the educational implications, the Imam has been used three educational actions to attain the monotheistic teleology, some are regarding the ideal conditions of the instructor, some are regarding the capacities of the pupil and some are regarding the content and means of education.